Profiling toxin genes and antibiotic resistance in Bacillus cereus isolated from pre-launch spacecraft - Mohammadi, Barakatullah; Gorkina, Natalia; Pérez-Reyes, Marco Esteban; Smith, Stephanie A. (Frontiers in Microbiology, 2023)
Characterization of the microbiomes of pre-launch spacecraft in spacecraft assembly facilities is an important step in keeping crews healthy during journeys that can last several hundred days in small artificial environments in space. B. cereus, a foodborne pathogenic bacterium, has the potential to be a significant source of food contamination in such environments. This bacterium is a spore-forming bacteria that resists different antimicrobial treatments in cleanrooms where spacecraft are assembled. This study evaluated 41 B. cereus isolates from four pre-launch spacecraft in spacecraft assembly facilities for their toxin gene profile and antibiotic resistance. Four enterotoxin genes (hlbC, cytK, nheA, and entFM) and two emetic toxin genes (ces and CER) were targeted for chromosomal DNA and plasmid DNA.Results showed 31.7%, 7.3%, 85%, and 41.5% of isolates contained hblC, cytK, nheA, and entFM, respectively, in chromosomal or plasmid DNA. Overall, 37 isolates (90.2%) showed at least one enterotoxin gene. The emetic toxin gene, ces, was detected in the plasmid DNA of three isolates (7.3%). The antibiotic resistance of isolates was evaluated by the Kirby-Bauer disk diffusion procedure. All the isolates exhibited 100% susceptibility to gentamicin, 97% were susceptible to clindamycin, and 95% to chloramphenicol, imipenem, tetracycline, and vancomycin. The overall susceptibility average is 51%. However, 98% of the isolates were resistant to β-lactam antibiotics, 97.5% were resistant to sulfamethoxazole/trimethoprim, and 80% were resistant to rifampin. This study provides important information on B. cereus isolates from spacecraft assembly facilities for use in microbial monitoring programs of spacecraft.